Wakaf: Tinjauan Fiqh, Dasar Hukum, dan Implementasinya di Indonesia - Yudi Permana; Meirani Rahayu Rukmanda (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
This article discusses waqf: fiqh review, legal basis and its implementation in Indonesia. This study was written using qualitative method with library study as its approach. Data source is in the form of library publications (Library Research). Data types are written narrations or documents contained in publication sources. Data collection techniques are carried out by tracking the sources of such publications. Data analysis techniques use description analysis. The results of this study show that waqf is reviewed in terms of fiqh, legal basis and its implementation in Indonesia has a mutually reinforcing relationship. From these findings, it can be concluded that waqf as an Islamic fiscal instrument has a strong foundation in terms of fiqh and ushul fiqh and its implementation, especially in Indonesia.